Laboratory Blood-Based Testing for Non-Lyme Disease Tick-Borne Infections at a National Reference Laboratory: A Seven-Year Experience. Issue 1 (4th October 2019) - Lee-Lewandrowski, Elizabeth; Chen, Zhen; Branda, John; Baron, Jason; Kaufman, Harvey W
Abstract: Objectives: We evaluated trends in non-Lyme disease tick-borne disease (NLTBI) testing at a national reference laboratory. Methods: Testing data performed at Quest Diagnostics during 2010 to 2016 were analyzed nationally and at the state level. Results: Testing and positivity for most NLTBIs increased dramatically from 2010 through 2016 based on testing from a large reference laboratory. The number of positive cases, though not as stringent as criteria for public health reporting, generally exceeds that reported by the Centers for Disease Control and Prevention. The frequency of NLTBI in the US is seasonal but testing activity and positive test results are observed throughout all months of the year. Positive results for NLTBI testing mostly originated from a limited number of states, indicating the geographic concentration and distribution of NLTBIs reported in this study. Conclusions: This report provides an important complementary source of data to best understand trends in and spread of NLTBI.